2022
DOI: 10.1111/nan.12819
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐6‐cleaved tau is relevant in Alzheimer's disease and marginal in four‐repeat tauopathies: Diagnostic and therapeutic implications

Abstract: Aim: Tau truncation (tr-tau) by active caspase-6 (aCasp-6) generates tau fragments that may be toxic. Yet the relationship between aCasp-6, different forms of tr-tau and hyperphosphorylated tau (p-tau) accumulation in human brains with Alzheimer's disease (AD) and other tauopathies remains unclear.Methods: We generated two neoepitope monoclonal antibodies against tr-tau sites (D402 and D13) targeted by aCasp-6. Then, we used five-plex immunofluorescence to quantify the neuronal and astroglial burden of aCasp-6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…While often classified as an executioner caspase, the function of caspase-6 (C6) in physiology and disease has remained enigmatic, and it has been suggested that C6 may act upstream of the other executioner caspases. , In addition to a putative amplifying role during apoptosis, C6 has been found to also possess nonapoptotic functions important for axon pruning and neuroinflammation. Finally, C6-mediated proteolysis has been implicated in the pathology of Huntington’s , and Alzheimer’s disease, in neuroinflammation generally and in nonalcoholic steatohepatitis …”
Section: Introductionmentioning
confidence: 99%
“…While often classified as an executioner caspase, the function of caspase-6 (C6) in physiology and disease has remained enigmatic, and it has been suggested that C6 may act upstream of the other executioner caspases. , In addition to a putative amplifying role during apoptosis, C6 has been found to also possess nonapoptotic functions important for axon pruning and neuroinflammation. Finally, C6-mediated proteolysis has been implicated in the pathology of Huntington’s , and Alzheimer’s disease, in neuroinflammation generally and in nonalcoholic steatohepatitis …”
Section: Introductionmentioning
confidence: 99%
“…Caspase-6- cleavage of tau at Asp402 generates a 1-402 fragment, associated with neurodegeneration, and the 403–441 with unknown functions [ 52 ]. Altogether, both active caspase-6 and tau truncated at Asp402 and Asp13 are present in neurofibrillary tangles, neuritic plaques, and neuropil threads in sporadic and familial AD but absent in brains without AD pathology [ 7 , 23 , 48 , 53 ].…”
Section: Caspase-cleaved Tau In Alzheimer’s Diseasementioning
confidence: 99%
“…Limited studies on cerebrospinal fluid (CSF) involving caspase-cleaved tau indicate that these fragments are released and can be identified in the CSF, potentially exhibiting a meaningful correlation with clinical deterioration [ 5 , 6 ]. Recent findings indicate that caspase-6 cleaved tau D13 and D402, commonly present in AD neurons, but rarely in 4-repeat tauopathies, only partially overlap with phospho-tau in the same neuron [ 7 ]. This implies that caspase-cleaved tau can signal tau pathology distinct from phospho-tau, highlighting a pathway that cannot be identified solely through phospho-tau-based biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Alzheimer's disease (AD), PD, multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS) are well-known neurological disorders [22][23][24][25], abnormal protein prenylation has been widely observed in patients with these diseases [26][27][28][29][30]. Recent evidence has shown that protein prenylation may be important for synaptic plasticity in the hippocampus and dendritic morphogenesis in the cortex [31,32].…”
Section: Introductionmentioning
confidence: 99%